The Role of Financial Inclusion and Competitive Advantage: Evidence from Iraqi Islamic Banks - Al-Duhaidahawi, Hayder M. Kareem; Zhang, Jing; Abdulreza, Mustafa S.; Harjan, Sinan Abdullah; Shah, Sayyed Sadaqat Hussain (International Journal of Economics and Financial Issues, 2019)
The purpose of this study is to investigate whether the financial Inclusion play a significant role in in achieving the competitive advantage in Iraqi banks particularly, Islamic banks. The target sample of this study is composed of customers using the technological instrument to access the services as achieving the financial Inclusion. Using a simple random sampling method to select the target sample of the study and designing a questionnaire for this purpose, (250) questionnaires were distributed and (20) were ignored, as they did not meet the respondents’ answers. Thus, the questionnaires analyzed were (230) questionnaires. Deceptive and regression analysis as statistical analysis are appropriate to the purposes of this study were carried out. The main results of this study were the significant effect of financial comprehensiveness on achieving the competitive advantage of institutions regarding customers. This study recommended that banking managerial staff has to focus on providing banking services using technological instrument because they constitute financial Inclusion and thus achieving the competitive advantage of banks, as well as certain programs are needed in the banks to raise the technological awareness of current and prospective customers. Keywords: Financial Inclusion, Competitive Advantage, Islamic Banks JEL Classifications: G29, L19, E59 DOI: https://doi.org/10.32479/ijefi.8080